THE EFFECT OF MAGNETIC DECLINATION CORRECTION ON SMARTPHONES COMPASS SENSORS IN DETERMINING QIBLA DIRECTION - Akhmad - Husein; Ahmad - Izzuddin; Muhammad Said Fadhel (Al-Hilal: Journal of Islamic Astronomy, 2021)
Qibla direction application on android phones generally utilizes a compass sensor (magnetic orientation) as a reference to determine the direction and detect qibla direction. The accuracy of the compass sensor in determining the direction of qibla is still doubtful, because the compass sensor is easily affected by the surrounding magnetic field, and the north direction shown by the compass sensor is not the geographical North direction but the north direction of the Earth's magnetic field. It certainly has a very influential effect on the accuracy of compass sensors in determining the direction of Qibla. The north direction produced by the compass sensor can be converted into the geographical north by adding a magnetic declination correction value. This study aims to analyze the effect of magnetic declination correction on the accuracy of compass sensors on android phones in determining qibla direction. The type of research used is a type of field research with a quantitative approach. In this study, observation was done by comparing the qibla direction of the android compass sensor with the qibla direction of a theodolite. The study showed that qibla direction measurement using android compass sensor with magnetic declination correction of angle difference (deviation) of 03° 55' 0.055" or 437.6815289 km, against qibla direction of the theodolite.